Light‐tunable optical cell manipulation via photoactive azobenzene‐containing thin film bio‐substrate. Issue 9 (13th July 2022) - Lefebvre, Olivier; Pinto, Sandra; Lahlil, Khalid; Peretti, Jacques; Smadja, Claire; Randriamampita, Clotilde; Lambert, Mireille; Fabbri, Filippo
Abstract: Live real‐time study of the local and collective cellular biomechanical responses requires the fine and selective manipulation of the cellular environment. One innovative pathway is the use of photoactive bio‐substrates such as azobenzene‐containing materials, which exhibit specific photomechanical properties, to optically trigger the local, mechanical stimulation of cells. Mechanically stimulated cells exhibit major morphological modifications and area shrinkage, which are dependent on the illumination. This demonstrates the capabilities of photomechanically active substrates to study the phenomena resulting from the mechanical interaction of cells with their environment. Abstract : We here demonstrate the use of photoactive azobenzene‐containing bio‐substrates, exhibiting specific photomechanical properties, to optically trigger the local, mechanical stimulation of cells. We achieve major light‐induced cells' morphological modifications and area shrinkage, which are dependent on the illumination conditions. This enables live real‐time study of local and collective cellular biomechanical responses, which requires the fine and selective manipulation of the cellular environment.